The price mechanism and the meaning of national income statistics - Usher, Dan (Oxford : Clarendon P., 1968)
The book is a computed statistics of real income of the underdeveloped countries including Thailand which in most cases are at variance with national income per head in $US.
Bibliographical footnotes.
usc 25/01/2019
Loans
Keywords: National income; Thailand